The Temporal Dynamics of Wish to Live, Wish to Die, and Their Short-Term Prospective Relationships With Suicidal Desire. Issue 3 (May 2023) - Oakey-Frost, Nicolas; Moscardini, Emma H.; Cowan, Tovah; Cohen, Alex; Tucker, Raymond P.
Highlights: Wish to live is concurrently protective of experiencing suicidal desire. Wish to die may drive some change in suicidal desire over time. Suicidal ambivalence may also drive change in suicidal desire. Wish to live and wish to die are distinct and must be considered in tandem. Abstract: The internal debate hypothesis (Kovacs & Beck, 1977) suggests that those at risk for suicidal thoughts and behaviors may experience fluctuations in both the wish to live (WTL) and wish to die (WTD). Previous research has investigated this hypothesis using various cross-sectional (Goods et al., 2019 [cf. Page & Stritzke, 2020]) and longitudinal methodologies (e.g., Bryan et al., 2016 ). No investigations have determined the within-day temporal dynamics of WTL and WTD using ecological moment assessment (EMA), however. N  = 49 undergraduate university students recruited from a research participant pool from a large southeastern university in the United States with a lifetime history of suicide ideation completed the current 10-day EMA investigation. Results demonstrated that WTL, WTD, and resulting suicidal ambivalence (i.e., relatively equal WTL/WTD ratings) demonstrated similar within-person person variability; however, WTD scores appeared to demonstrate higher average variability compared to WTL and ambivalence scores. Although state WTL and WTD were concurrently related to state suicidal desire, only WTD prospectively predicted suicidal desire when controlling for the influence of the outcome variable at the previous timepoint. Ambivalence scores also prospectively predicted suicidal desire when controlling for suicidal desire at the previous timepoint. Results support the clinical and theoretical utility of separate WTL and WTD assessment. WTD was relatively stable within this sample but may be closely related to risk for future suicidal thinking. Changes in WTL may reduce state risk for suicidal desire but could be more trait-like in nature compared to WTD. Future research that investigates these hypotheses should consider the study limitations outlined.